Impact of Bullying on Academic performance and mental Well-Being Among Female students - Dey, Monami; Srivastava, Kiran (Journal of Neonatal Surgery, 2025)
Bullying is a pervasive issue affecting millions of students worldwide, with girl students being disproportionately affected. This study investigates the impact of bullying on girl students’ academic performance and mental well-being. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews. The study reveals that bullying has a significant negative impact on girl students’ academic performance, leading to decreased motivation, lower grades, and increased absenteeism. Furthermore, bullying was found to have severe consequences on girl students’ mental well-being, including increased anxiety, depression, and low self- esteem. The study highlights the need for schools to implement effective anti-bullying policies and programs to create a safe and supportive learning environment. The findings of this study have implications for educators, policymakers, and parents, emphasizing the importance of addressing bullying to promote girl students’ academic success and mental well-being.